(untitled) (KONFERENSIYA, 2025)
This article examines memes as cultural texts embedded in the social, political, and ideological dynamics of digital communication. Moving beyond their humorous surface, memes are positioned as semiotic artifacts that perform identity work, negotiate cultural power, and structure collective meaning-making within online communities. By drawing on multimodal discourse analysis, ethnography of communication, and cultural theory, the study analyzes memes as instruments of symbolic representation, ideological reproduction, and digital folk creativity. It highlights how visual discourse enables communities to co-create cultural narratives, contest dominant ideologies, and sustain evolving digital identities through shared symbols and visual metaphors